Innovation on Wings: Nonstop Flights and Firm Innovation in the Global Context - Bahar, Dany; Choudhury, Prithwiraj; Kim, Do Yoon; Koo, Wesley W. (Management Science, 2023)
We study whether, when, and how better connectivity through nonstop flights leads to positive innovation outcomes for firms in the global context. Using unique data of all flights emanating from 5,015 airports around the globe from 2005 to 2015 and exploiting a regression discontinuity framework, we report that a 10% increase in nonstop flights between two locations leads to a 3.4% increase in citations and a 1.4% increase in the production of collaborative patents between those locations. This effect is driven primarily by firms as opposed to academic institutions. We further study the characteristics of firms and firm locations that are salient to the relation between nonstop flights and innovation outcomes across countries. Using a gravity model, we posit and find that the positive effect of nonstop flights on innovation is stronger for firms and subsidiaries with greater innovation mass (e.g., stocks of inventors and R&D spending), located in innovation hubs or countries that are deemed technology leaders, and that are separated by large cultural or temporal distance. This paper was accepted by Alfonso Gambardella, business strategy. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.4682 .